Adverse psychological outcomes following colposcopy and related procedures: a systematic review. (22nd June 2015) - O'Connor, M; Gallagher, P; Waller, J; Martin, CM; O'Leary, JJ; Sharp, L
Abstract : Background: Although colposcopy is the leading follow‐up option for women with abnormal cervical cytology, little is known about its psychological consequences. Objectives: We performed a systematic review to examine: (1) what, if any, are the adverse psychological outcomes following colposcopy and related procedures; (2) what are the predictors of adverse psychological outcomes post‐colposcopy; and (3) what happens to these outcomes over time. Search strategy: Five electronic databases (PubMed, PsychINFO, CINAHL, Web of Science, Scopus) were searched for studies published in English between January 1986 and February 2014. Selection criteria: Eligible studies assessed psychological wellbeing at one or more time‐points post‐colposcopy. Data collection and analysis: Two reviewers independently screened titles and abstracts. Full texts of potentially eligible papers were reviewed. Data were abstracted from, and a quality appraisal performed of, eligible papers. Main results: Twenty‐three papers reporting 16 studies were eligible. Colposcopy and related procedures can lead to adverse psychological outcomes, particularly anxiety. Ten studies investigated predictors of adverse psychological outcomes; management type and treatment had no impact on this. Seven studies investigated temporal trends in psychological outcomes post‐colposcopy; findings were mixed, especially in relation to anxiety and distress. Studies were methodologically heterogeneous. Conclusions: Follow‐up investigations and procedures for abnormal cervical cytology can cause adverse psychological outcomes among women. However, little is known about the predictors of these outcomes or how long they persist. There is a need for a more standardised approach to the examination of the psychological impact of colposcopy, especially longer‐term outcomes. Tweetable abstract: Follow‐up investigations for abnormal cervical cytology can cause adverse psychological outcome among women. Tweetable abstract: Follow‐up investigations for abnormal cervical cytology can cause adverse psychological outcome among women.